Ethnomathematics Approach: A Strategy to Improve Mathematical Problem Solving Skills of Elementary School Students - Mutaqin, Ejen Jenal; Herman, Tatang; Wahyudin, Wahyudin; Agistina, Ghania Nurul; Aziz, Asep Kamal Abdul (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
This study explores the impact of an ethnomathematics-based approach on elementary students’ abilities in mathematical problem-solving. Employing a quasi-experimental design with a posttest-only control group, the research involved two equivalent classes at MI An Nur VI in Garut Regency. The experimental group was taught using an ethnomathematics approach incorporating Sundanese cultural elements into geometry lessons, while the control group received conventional instruction. Statistical results revealed a significant difference in posttest scores, favoring the experimental group. These findings suggest that ethnomathematics effectively enhances students’ problem-solving capabilities by offering contextual and culturally relevant learning experiences. The study supports culturally responsive pedagogy and aligns with the Merdeka Curriculum’s vision of inclusive, student-centered education.Penelitian ini bertujuan untuk mengkaji pengaruh pendekatan etnomatematika terhadap kemampuan pemecahan masalah matematis siswa sekolah dasar. Metode yang digunakan adalah kuasi eksperimen dengan desain posttest only control group, melibatkan dua kelas paralel di MI An Nur VI, Kabupaten Garut. Kelas eksperimen mengikuti pembelajaran berbasis etnomatematika yang mengintegrasikan unsur budaya Sunda ke dalam materi geometri, sedangkan kelas kontrol memperoleh pembelajaran secara konvensional. Analisis statistik menunjukkan perbedaan signifikan antara kedua kelompok, dengan skor posttest siswa di kelas eksperimen lebih tinggi. Hasil ini menunjukkan bahwa pendekatan etnomatematika mampu meningkatkan keterampilan pemecahan masalah matematis melalui pembelajaran yang kontekstual, bermakna, dan selaras dengan budaya lokal. Temuan ini memberikan kontribusi terhadap praktik pembelajaran berbasis kearifan lokal dan mendukung penerapan Kurikulum Merdeka yang berfokus pada pembelajaran yang inklusif dan berpusat pada peserta didik.